Risk factors for overuse injuries in short- and long-distance running: A systematic review - Dennis van Poppel; Maarten van der Worp; Anouk Slabbekoorn; Sylvia S.P. van den Heuvel; Marienke van Middelkoop; Bart W. Koes; Arianne P. Verhagen; Gwendolyne G.M. Scholten-Peeters (Elsevier, 2021)
Purpose: The aim of this study was to review information about risk factors for lower extremity running injuries in both short-distance (mean running distance ≤20 km/week and ≤10 km/session) and long-distance runners (mean running distance >20 km/week and >10 km/session). Methods: Electronic databases were searched for articles published up to February 2019. Prospective cohort studies using multivariable analysis for the assessment of individual risk factors or risk models for the occurrence of lower extremity running injuries were included. Two reviewers independently selected studies for eligibility and assessed risk of bias with the Quality in Prognostic Studies Tool. The GRADE approach was used to assess the quality of the evidence. Results: A total of 29 studies were included: 17 studies focused on short-distance runners, 11 studies focused on long-distance runners, and 1 study focused on both types of runners. A previous running-related injury was the strongest risk factor for an injury for long-distance runners, with moderate-quality evidence. Previous injuries not attributed to running was the strongest risk factor for an injury for short-distance runners, with high-quality evidence. Higher body mass index, higher age, sex (male), having no previous running experience, and lower running volume were strong risk factors, with moderate quality evidence, for short-distance runners. Low-quality evidence was found for all risk models as predictors of running-related injuries among short- and long-distance runners. Conclusion: Several risk factors for lower extremity injuries have been identified among short- and long-distance runners, but the quality of evidence for these risk factors for running-related injuries is limited. Running injuries seem to have a multifactorial origin both in short- and long-distance runners.